Innovation and entrepreneurship in education - Papadopoulos, Pantelis M.; Burger, Roland; Faria, Ana (Advances in digital education and lifelong learning ;, 2016)
This book explores the concepts of innovation and entrepreneurship through multiple lenses in the context of education. Mixing equal parts of theory and practice, this volume takes a closer look on how innovation and entrepreneurship are approached around the globe as disciplines, methods, and mindsets. Focusing on ubiquitous learning and transcending the borders of formal, informal, and non-formal learning, the book presents theoretical models and case studies of initiatives, practices, and projects on how innovative pedagogies and ICT could support the development of innovation and entrepreneurial skills for business and everyday life. Featured examples illustrate how emerging learning theories and technology could become powerful agents in nurturing creativity, self-efficacy, problem-solving, social connectedness, and inclusion. The book provides a glimpse at the state-of-the-art in innovation and entrepreneurship in education as seen through the latest academic studies and business currents.